Integrating Values in the Care Giving Activity from the Professional Point of View - Juan Carlos Delgado-Antolín (Universidad de Antioquia, 2014)
Nurses trained more and more on scientific evidence, often focus their actions based fundamentally on scientific fact, leaving aside other important knowledge that intervene in the care giving relation: communication, personal relationships, respect in the relationship, and knowing all the values implied in said relationship. It is about these values and on their importance within care upon which the author reflects in this article, until concluding on how we can integrate values to the care giving activity.